İNEKLERDE TOHUMLAMA SONRASI UYGULANAN LESİRELİN ASETAT (GNRH ANALOGU)'IN GEBELİK ÜZERİNE ETKİSİ - CAN, COŞKUN (Fırat Üniveristesi, 2015)
Bu tezde, ineklere suni tohumlama ile birlikte farklı yollardan lesirelin asetat enjeksiyonlarının gebelik oranları üzerindeki etkisi araştırıldı. Materyal olarak postpartum 50-120. günler arasında kendiliğinden kızgınlığa gelen, düzenli aralıklarla seksüel siklus gösteren ve bu süreçte herhangi bir klinik bozukluk göstermeyen farklı ırk ve yaştan 180 inek kullanıldı. Materyali oluşturan inekler rastgele 4 gruba ayrıldı. A grubunda bulunan (n= 50) hayvanlara suni tohumlamadan hemen sonra 50 µg lesirelin asetat, B grubu (n=40), hayvanlara 2 ml serum fizyolojik üst epidural boşluğa uygulandı. C grubu (n=50), hayvanlara suni tohumlamadan hemen sonra 50 µg lesirelin asetat, D grubuna (n=40) ise, 2 ml serum fizyolojik kas içi olarak enjekte edildi. A ve B grubunda hayvanların gebelik oranları (sırasıyla % 64, % 45) arasında farklılığın olduğu (P<0,05) görüldü. Kas içi uygulama yapılan C ve D grubunda gebelik oranları (sırasıyla % 60, % 52,5) yönüyle farkın olmadığı (P>0,05) belirlendi. Ayrıca, epidural ve kas içi GnRH uygulanan gruplar arasında da istatistiki bir farkın (P>0,05) olmadığı tespit edildi. Sonuç olarak, yapılan tezde kendiliğinden östrüse gelen ineklere tohumlama ile birlikte epidural yolla uygulanan GnRH enjeksiyonlarının gebelik oranlarını artırmada faydalı olacağı kanaatine varıldı.

In the present thesis the effects of lecirelin acetate injections applied in different ways along with the artificial insemination on the pregnancy rate of cows were investigated. As a material, 180 cows showing the spontaneous oestrus between 50-120 days after parturation and having the sexual cycle at regular intervals and not showing any clinical disorders during the treatment process were used. The cows were randomly divided into 4 groups. A, B, C and D. Immediately after the artificial insemination 50 µg lecirelin acetate was injected to the sacrococcygeal epidural space of the animals in the group A (n = 50). The animals in the group B (n = 40) were injected with 2 ml physiological saline solution by the same route applied to the animals in the group A. The animals in the group C (n = 50) were injected with 50 µg lecirelin acetate by way of intramuscular immediately after the artifical insemination. The animals in the group D (n = 40) were injected with 2 ml physiological saline solution by the same route applied to the animals in the group C. There was a significant difference (P<0,05) between the group A and B by the pregnancy rates of 64% and 45%, respectively. It was detected that there was no significant difference (P>0,05) in the pregnancy rates of the groups C and D (60% and 52,5%, respectively). In addition, no significant difference (P>0,05) was observed between the group A (applied epidural GnRH) and B (applied intramuscular GnRH). As a result, it was concluded that administration of epidural GnRH along with the artifical insemination to cows showing spontaneous oestrus maybe useful for increase the pregnancy rates.
Effect on pregnancy rates of injected lecirelin acetate (GnRH analogue) after insemination in the cows
Keywords: Veteriner Hekimliği